The Religious Experience of the Church and the Experience of National Community in the Writings of Joseph Ratzinger–Benedict XVI - Woźniak, Jakub J. (Studia Gdańskie, 2019)
The main subject covered in this paper is the coexistence of the religious experience of the Church and the experience of national community in the teaching of Joseph Ratzinger–Benedict XVI. The starting point is the understanding of experience in the writings of Joseph Ratzinger–Benedict XVI. In his view, experience manifests itself in three ways: through faith and liturgy, through testimony and through saints. This, in turn, translates to the national experience, which encompasses such areas as culture and academia, religious and universal values, natural law, family and education, and the principles of subsidiarity and solidarity in development and progress. The interdependence between the Church and the national community reflected in the works of Joseph Ratzinger–Benedict XVI highlights the need for these two institutions to work together towards the common good of those who constitute the Church and those who constitute the nation, regardless of their religious beliefs or political convictions. Throughout Cardinal Ratzinger’s teaching, one can observe that the religious experience of the Church provides a starting point for the national experience that manifests itself in the brotherhood of all people.